Answer:
-1
Explanation:
To solve this word problem, we need to convert it into an equation. Let's first dissect the problem:
"The sum of six times a number and 1" -- since "sum" means addition, and "6 times" means 6 multiplied by some number, we can write this as: 6x + 1, where x stands for the unknown number
"is equal to five times the number" -- since "equals" means "=" and five times the number means 5x, where x stands for that same unknown number, we can write as: = 5x
Put it all together and we have
6x + 1 = 5x
Now we can solve our equation.
First, we need to get all of the like terms on each side of the equal sign. To do this, we will first subtract 1 from both sides:
6x + 1 - 1 = 5x - 1, which gives us 6x = 5x - 1
Next, we will subtract 5x from both sides:
6x - 5x = 5x - 5x - 1, giving us x = -1
-1 is the number
hope this helps